'Not so Much Learning to Speak Latin, but Speaking to Learn it'. Action Research on the Use of Conversational, Spoken Latin in the UK Secondary School Classroom. Issue 38 (27th November 2018) - Sinclair, James
Abstract : I undertook research into the use of conversational, spoken Latin in the UK classroom, due to my intention to answer three specific research questions. Firstly, I wanted to find out how easy it is for the contemporary Classics teacher to implement communicative approaches to the teaching of Latin. Secondly, I wished to discover what techniques the Classics teacher can adopt to implement communicative approaches to the teaching of Latin, within the framework of active, oral communication in Latin. Thirdly, I wanted to consider how positive is the attitude of students engaging with communicative approaches to the teaching of Latin. I was introduced to this area of research on my PGCE course of study at Cambridge University. Furthermore, I was especially inspired by the scholarship of Coffee (2012), King (2011), Lloyd (2016), Patrick (2015), Rasmussen (2015) and Tunberg (2011) who have written so positively about the unique ability of communicative approaches to unlock the joy of experiencing and employing the Latin language for individuals of all ages.